2020
DOI: 10.1038/s41531-020-00133-y
|View full text |Cite
|
Sign up to set email alerts
|

Dysfunction in superior frontal gyrus associated with diphasic dyskinesia in Parkinson’s disease

Abstract: Alterations in brain function in Parkinson’s disease (PD) patients with diphasic dyskinesia have not been investigated. We aimed to explore the alterations in regional brain function. Each of 53 levodopa (LD)-treated PD patients had two resting-state functional magnetic resonance imaging (rs-fMRI) scans in the same morning, before and after taking LD. The regional homogeneity (ReHo) approach was used to reveal local synchronization changes. Two-way factorial repeated measures analysis of covariance, with group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…Based on the results of Li et al (2013) and Shen et al (2020) , the SFG, a connecting node between the central executive network and default mode network (DMN), is linked to the cognitive control network and the cognitive executive network. The MFG, a location where the ventral and dorsal attention networks converge, is involved in language fluency, object naming and directed attention and is part of the cognitive executive network ( Japee et al, 2015 ; Viñas-Guasch and Wu, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the results of Li et al (2013) and Shen et al (2020) , the SFG, a connecting node between the central executive network and default mode network (DMN), is linked to the cognitive control network and the cognitive executive network. The MFG, a location where the ventral and dorsal attention networks converge, is involved in language fluency, object naming and directed attention and is part of the cognitive executive network ( Japee et al, 2015 ; Viñas-Guasch and Wu, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…In line with our results, previous imaging studies showed a possible relationship between dyskinesias and SFG. An fMRI study reported that an abnormal local synchronization in the left SFG is closely associated with the development of diphasic dyskinesia in patients with PD [38]. Patients with schizophrenia, with tardive dyskinesia, showed a reduced SFG volume, which correlated with the severity of their dyskinesia [25].…”
Section: Discussionmentioning
confidence: 99%
“…ReHo is based on a data-driven approach and thus requires no prior knowledge and has good test-retest reliability ( Zuo et al, 2013 ). ALFF and ReHo analysis has been used to study migraine in our previous study ( Liu et al, 2015 ), and other diseases like premenstrual syndrome ( Pang et al, 2020 ), Alzheimer’s disease ( Li et al, 2020a ), and Parkinson’s disease ( Shen et al, 2020 ), among others.…”
Section: Introductionmentioning
confidence: 99%